2016
DOI: 10.1063/1.4962274
|View full text |Cite
|
Sign up to set email alerts
|

Effective material parameter retrieval of anisotropic elastic metamaterials with inherent nonlocality

Abstract: In this paper, the scattering (S-) parameter retrieval method is presented specifically for anisotropic elastic metamaterials; so far, no retrieval has been accomplished when elastic metamaterials exhibit fully anisotropic behavior. Complex constitutive property and intrinsic scattering behavior of elastic metamaterials make their characterization far more complicated than that for acoustic and electromagnetic metamaterials. In particular, elastic metamaterials generally exhibit anisotropic scattering behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The other method is the S-parameter retrieval method (SPRM) that numerically extracts effective parameters through scattering components by a toy model. Notice that only a handful of studies on SPRM in EMTMs exists, and one can be found that effective mass density and stiffness have been investigated considering full anisotropy with intrinsic nonlocal responses in the system [54].…”
Section: Representative Studies Of Locally Resonant Elastic Metamatermentioning
confidence: 99%
“…The other method is the S-parameter retrieval method (SPRM) that numerically extracts effective parameters through scattering components by a toy model. Notice that only a handful of studies on SPRM in EMTMs exists, and one can be found that effective mass density and stiffness have been investigated considering full anisotropy with intrinsic nonlocal responses in the system [54].…”
Section: Representative Studies Of Locally Resonant Elastic Metamatermentioning
confidence: 99%
“…Having in mind the x 1 -symmetry of the system, which leads to κ 35 being an odd function of s 2 , the values of µ 55 and η 33 can be determined exactly from Equations (38), (39). However, the value of µ 54 will be a function of κ 35 as:…”
Section: Transfer Matrix Of Layered Structures For Oblique Sh Wavesmentioning
confidence: 99%
“…In these works, the focus has been on propagation of pressure acoustic waves and the effect of microstructure on effective bulk modulus and density. Lee et al [39], extended the work in [34] to mechanical metamaterials, where the elasticity tensor components, beyond just the bulk modulus, are incorporated. Recently a mathematically exact theory for Willis-type media has been developed along with a matching field integration technique for normal incidence in [40], where transfer matrix method (TMM) is used to calculate the scattering exactly.…”
Section: Introductionmentioning
confidence: 99%
“…4(a)]. The void slits must be tilted at a certain angle with respect to the wave incidence direction for nonzero C 16 values [26]. The weakly and strongly coupled EMM layers consist of unit cells with 8 and 6 periods, respectively.…”
mentioning
confidence: 99%
“…Fully detailed microstructures were considered for the finite element simulation [16]. The S-parameter method [26] was used to retrieve the C ij of the EMMs, which were used to calculate f theory . The theoretical TFPR frequency f theory predicted by Eq.…”
mentioning
confidence: 99%